2022
DOI: 10.3390/agronomy12051033
|View full text |Cite
|
Sign up to set email alerts
|

Betalain Content and Morphological Characteristics of Table Beet Accessions: Their Interplay with Abiotic Factors

Abstract: Table beet (Beta vulgaris L.) is a source of the natural red-colored food dye (E162), highly demanded for the broad spectrum of its biological activity. The relevance of this study is dictated by the lack of knowledge about the dynamics of changes in the crop’s betalain content during the growing season, which impedes identifying the optimal timing of harvesting in order to obtain the dye. This paper presents the results of research into betacyanins (BC) and betaxanthins (BX), separately in the peel and flesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
2
8
0
2
Order By: Relevance
“…Watari, Ikeura, Tsuge, & Motoki (2017) stated that the highest betacyanin was produced during seedling phase that might reach 37.2 mg/100 g FW, followed by a planting phase at 31.1 mg/100 g FW, and then tuber enlargement phase and the growth late vegetative phase at 24.5 mg/100g FW. This furtherly strengthens (Sokolova, Shvachko, Mikhailova, & Popov, 2022) findings that betacyanin biosynthesis in red beet was dynamic, changes during ontogenesis and depends on genetic, environmental and cultivation management factors.…”
Section: Component Of An Equation Controlsupporting
confidence: 86%
See 2 more Smart Citations
“…Watari, Ikeura, Tsuge, & Motoki (2017) stated that the highest betacyanin was produced during seedling phase that might reach 37.2 mg/100 g FW, followed by a planting phase at 31.1 mg/100 g FW, and then tuber enlargement phase and the growth late vegetative phase at 24.5 mg/100g FW. This furtherly strengthens (Sokolova, Shvachko, Mikhailova, & Popov, 2022) findings that betacyanin biosynthesis in red beet was dynamic, changes during ontogenesis and depends on genetic, environmental and cultivation management factors.…”
Section: Component Of An Equation Controlsupporting
confidence: 86%
“…Red beet betacyanin is the only source of betalain which is permitted as a food additive (Polturak & Aharoni, 2018) with code Natural Red 33 in USA or E162 in european countries (da Silva et al, 2019)the antioxidant power and health-promoting properties of this pigment have been disregarded, perhaps due to the difficulty in obtaining a stable chemical compound, which impairs its absorption and metabolism evaluation. Herein, betanin was purified by semi-preparative HPLC-LC/MS and identified by LC-ESI(+ and for its broad spectrum of biological activity (Sokolova, Shvachko, Mikhailova, & Popov, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betalain accumulation could make the amaranth leaves red ( Barba-Espin et al., 2018 ; Fan et al., 2020 ), which is determined by environmental conditions and transcription factors ( Erika et al., 2018 ; Preczenhak et al., 2019 ; Guerrero-Rubio et al., 2020 ; Sakuta et al., 2021 ; Sokolova et al., 2022 ). Our previous studies have indicated that various environmental factors and hormones (GA 3 and 2,4-D) influence betalain biosynthesis ( Xiao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence also supported our hypothesis that white roots are a general characteristic of beetroot root systems at least at early growing stage (28 days), although the abundance of white roots did differ between cultivars. The root colour of beetroot is determined by the contents of betalain, whose biosynthesis has been proved to be a synthetic consequence of genetics and abiotic conditions [ 3 , 22 ]. Root colour has been used as an indicator of root age in many studies, where the root colour changes are linked to root senescence [ 18 ].…”
Section: Discussionmentioning
confidence: 99%